2022
DOI: 10.3389/fnbeh.2022.886634
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Causes Persistent Increases in Alzheimer’s Tau Pathology in Female 3xTg-AD Mice: A Potential Role for Lysosomal Impairment

Abstract: Epidemiological studies have found that heavy alcohol use is associated with increased risk for Alzheimer’s disease (AD), with frequent drinking earlier in adulthood increasing risk. The increases in neuroinflammation featured in both heavy alcohol use and AD may be partially responsible for this link. However, it is unknown if abstinence mitigates this risk. We hypothesized that binge ethanol during mid adult life would persistently increase AD pathology even after prolonged abstinence. Male and female 3xTg-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…The effects of ABAE on adult behaviors are not limited to adult alcohol consumption. ABAE increases the risk for psychological disorders (depression, anxiety disorders, and schizophrenia), neurodegenerative disorders (AD, PD, and other dementia-related illnesses), and auto-immune diseases during adulthood (Harwood et al, 2010 ; Langballe et al, 2015 ; Schwarzinger et al, 2018 ; Coleman et al, 2019 ; Barnett et al, 2022 ; Tucker et al, 2022 ). ABAE also affects the reproductive system (hypogonadism and reduced sperm viability (Duca et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of ABAE on adult behaviors are not limited to adult alcohol consumption. ABAE increases the risk for psychological disorders (depression, anxiety disorders, and schizophrenia), neurodegenerative disorders (AD, PD, and other dementia-related illnesses), and auto-immune diseases during adulthood (Harwood et al, 2010 ; Langballe et al, 2015 ; Schwarzinger et al, 2018 ; Coleman et al, 2019 ; Barnett et al, 2022 ; Tucker et al, 2022 ). ABAE also affects the reproductive system (hypogonadism and reduced sperm viability (Duca et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of adolescent-binge alcohol exposure (ABAE) is not specific to alcohol consumption behaviors. Excessive adolescent alcohol consumption is associated with higher risk of developing mood disorders (depression and anxiety disorders), neurodegenerative diseases [e.g., Alzheimer’s disease (AD), Parkinson’s disorder (PD), other dementia-related Illnesses], other mental health disorders (schizophrenia), and auto-immune diseases during adulthood (Harwood et al, 2010 ; Langballe et al, 2015 ; Schwarzinger et al, 2018 ; Coleman et al, 2019 ; Barnett et al, 2022 ; Tucker et al, 2022 ). Therefore, developing interventions that prevent ABAE will benefit society by reducing adult rates of AUD and reducing the risk factors of several other disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Our P301S animals likely had tau lesions present during the latter part of the IA paradigm and at the 7-month time point used in our physiological studies. While we did not evaluate the effects of long-term ethanol consumption on tau accumulation, previous work using the triple transgenic AD mouse model (3xTg-AD), which includes a knock-in P301L tau variant along with additional AD-associated presenilin and amyloid precursor protein variants (Oddo et al, 2003), has demonstrated increased phosphorylated tau accumulation in the hippocampus, piriform cortex, medial prefrontal cortex, entorhinal cortex, and amygdala following both binge and long-term ethanol consumption (Barnett et al, 2022; Hoffman et al, 2019; Tucker et al, 2022). Future studies will need to investigate the impacts of alcohol consumption on tau accumulation in the LC itself.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption throughout life may enhance the risk for developing dementia from tauopathy disorders, including AD and frontotemporal dementia (FTD) (Heymann et al, 2016; Peng et al, 2020; Rehm et al, 2019; Tyas, 2001; Wang et al, 2021). Mouse models of AD have also demonstrated increased AD-associated pathology due to alcohol consumption (Barnett et al, 2022; Hoffman et al, 2019; Tucker et al, 2022). While there appears to be a clear linkage between alcohol use, the ageing brain, and tauopathies including FTD and AD, there has been relatively little work examining the interaction of tau and alcohol in specific neural circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, alcohol consumption has been linked to an increased risk of dementia in individuals with a genetic predisposition to AD [78,79]. Recent data from preclinical studies demonstrate that the consequences of adult or developmental EtOH exposure resemble advanced brain aging or produces accelerated AD-related pathology in transgenic models with AD-related transgenes [80][81][82][83]. Advanced aging, AD, and AUD have some overlapping neuropathological sequelae: upregulation of proinflammatory markers, suppressed hippocampal neurogenesis, suppression of basal forebrain cholinergic phenotype, and altered pro-and mature NT levels-as well as a change in the ratio of Trk to p75 NTRs [84][85][86][87][88].…”
Section: Proposed Mechanism Of the Regulation Of Phasic And Tonic Ace...mentioning
confidence: 99%